(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the scientific works of Bubuina Omurzakovna Oruzbaeva, an outstanding scientist, the first kyrgyz woman to defend a doctorate in philology, professor, academician of the National Academy of Sciences. It explored such issues as ancient turkic written monuments in kyrgyz linguistics, the history of the kyrgyz literary language, the relationship of languages (kyrgyz and russian), the ratio of simple language and literary language, grammar of the kyrgyz language (morphology and word formation), lexicology and lexicography, bilingualism and interference. Along with this, Bubuina Omurzakovna’s works on the history, grammar, lexicology, vocabulary and terminology of the kyrgyz language, which were the first to be developed at the scientific level, and the most important theoretical issues proposed by her, were considered. The great contribution of kyrgyz linguistics to the training of students was also noted.